2014
DOI: 10.1016/j.ccr.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Merlin/NF2 Loss-Driven Tumorigenesis Linked to CRL4DCAF1-Mediated Inhibition of the Hippo Pathway Kinases Lats1 and 2 in the Nucleus

Abstract: It is currently unclear if Merlin/NF2 suppresses tumorigenesis by activating upstream components of the Hippo pathway at the plasma membrane or by inhibiting the E3 ubiquitin ligase CRL4DCAF1 in the nucleus. We found that de-repressed CRL4DCAF1 promotes YAP and TEAD-dependent transcription by ubiquitylating and thereby inhibiting Lats1 and 2 in the nucleus. Genetic epistasis experiments and analysis of tumor-derived missense mutations indicate that this signaling connection sustains the oncogenicity of Merlin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
202
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(213 citation statements)
references
References 43 publications
9
202
1
1
Order By: Relevance
“…A WW domain-containing HECT class E3 ubiquitin ligase, ITCH, ubiquitinates LATS1 and promotes cell growth and survival (Ho et al 2011;Salah et al 2011). Another E3 ubiquitin ligase, CRL4 (DCAF1), which is activated in NF2-deficient tumor cells, inhibits LATS1 and LATS2 by ubiquitination in the nucleus (Li et al 2014b). Ubiquitination of LATS1/2 also plays a role in stress response and differentiation.…”
Section: Spatial Regulation Of Mst and Latsmentioning
confidence: 99%
“…A WW domain-containing HECT class E3 ubiquitin ligase, ITCH, ubiquitinates LATS1 and promotes cell growth and survival (Ho et al 2011;Salah et al 2011). Another E3 ubiquitin ligase, CRL4 (DCAF1), which is activated in NF2-deficient tumor cells, inhibits LATS1 and LATS2 by ubiquitination in the nucleus (Li et al 2014b). Ubiquitination of LATS1/2 also plays a role in stress response and differentiation.…”
Section: Spatial Regulation Of Mst and Latsmentioning
confidence: 99%
“…15,16 In Drosophila, Merlin cooperates with another FERM domain protein, Expanded, to accelerate endocytosis of specific receptors, including mitogenic receptors. 17 In addition, the role of Merlin in Hippo signaling, which is responsible for control of cell proliferation and organ size, has been intensively studied.…”
mentioning
confidence: 99%
“…Notably, LATS1 is cytoplasmic in luminal cells, which may prevent it from facilitating ERα degradation. Britschgi et al [5] speculate that cytosolic LATS can suppress YAP/ TAZ activity in luminal cells, although previous findings have indicated that LATS1/2 are predominantly active in the nucleus [7]. Further work is needed to fully understand in which subcellular compartment LATS1/2 are activated and target YAP in mammary stem cells and their progeny.…”
mentioning
confidence: 99%
“…In addition to restraining YAP activation, which drives stem cell self-renewal, LATS1/2 facilitate ERα ubiquitylation by the E3 ligase CRL4 DCAF1 , thereby suppressing luminal progenitor specification and differentiation. Adding to this complexity, NF2/Merlin suppresses the ability of CRL4 DCAF1 to target LATS, providing a mechanism for activation of YAP in NF2-mutant tumors [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation